Integrating health and agriculture to maximize the nutritional impact of orange-fleshed sweetpotato: The Mama SASHA proof-of-concept project in Western Kenya - International Potato Center (2011)
Unexpectedly high rates of participation from pregnant women during the pilot phase suggest that the integration of orange-fleshed sweetpotato (OFSP), nutrition education and vine distribution into antenatal care is reaching target audiences. It promises to not only increase use and awareness of the benefits of OFSP among targeted populations but also attract more women into timely antenatal care services.